2011
DOI: 10.1016/j.apor.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prediction of vortex-induced vibrations of variable-tension vertical risers in linearly sheared currents

Abstract: Many studies have tackled the problem of vortex-induced vibrations (VIV) of a vertical riser with a constant tension and placed in uniform currents. In this study, attention is focused on the cross-flow VIV modelling, time-domain analysis and prediction of variable-tension vertical risers in linearly sheared currents. The partial-differential equation governing the riser transverse motion is based on a flexural tensioned-beam model with typical pinned-pinned supports. The hydrodynamic excitation model describi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…Similarly, spatial variations of the cable's tension (for example due to gravity and/or free end conditions) is expected to impact the structure's dynamics, in particular by localizing vibrations in regions with lower tension. This second configuration has so far received little attention [15,16]. The present paper thus discusses an experimental investigation of the VIV of a hanging string, where gravity-induced tension does vary from bottom to the top.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, spatial variations of the cable's tension (for example due to gravity and/or free end conditions) is expected to impact the structure's dynamics, in particular by localizing vibrations in regions with lower tension. This second configuration has so far received little attention [15,16]. The present paper thus discusses an experimental investigation of the VIV of a hanging string, where gravity-induced tension does vary from bottom to the top.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the setting depth of conductor in deepwater drilling directly affects the mechanical stability of subsea wellhead. If the depth design is relatively shallower, it will lead to instability of subsea wellhead; on the contrary, if the design depth is deeper, although it can ensure the security of subsea wellhead, it will result in a waste of resources, and may cause the conductor can not be to the specified depth [15][16][17]. Through investigation of currently used methods of setting depth of conductor for deepwater drilling [9][10][11][12], we found that the calculated value is a single value, while there are many uncertainties in the parameters of subsea shallow strata in deepwater drilling.…”
Section: Introductionmentioning
confidence: 94%
“…Chang and Isherwood [7] developed a time domain VIV prediction code using wake-oscillator model and vortex tracking model. Srinil [8] simulated Tognarelli's laboratory test model [9] using wake-oscillator model by assuming the riser response frequency locked in the Strouhal frequency associated with the maximum current velocity. Cheng et al [10,11] carried out lots of validation works using different riser models.…”
Section: Introductionmentioning
confidence: 99%